2013
DOI: 10.1159/000353633
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Intrauterine Growth Restriction: Cardiovascular Disorders

Abstract: In the modern world, cardiovascular disorders are the leading cause of mortality in developed countries, which in most cases undergo a long subclinical phase that can last decades before the first clinical symptoms appear. Aside from the well-known risk factors related to lifestyle and genetics, there is growing evidence that in a proportion of cases, the predisposition to cardiovascular disease lies in prenatal life. Moreover, numerous historical cohort studies and animal models have shown a clear association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 119 publications
(135 reference statements)
1
69
0
5
Order By: Relevance
“…Defects in placental vascular development can cause embryonic death and abnormal organogenesis, can negatively affect fetal growth and can confer a higher risk of disease in the postnatal life (Barker et al, 1989). For example, defective patterning of the fetoplacental vasculature, also known as the labyrinth, results in abnormal heart development in mouse (Shaut et al, 2008) and human (Demicheva and Crispi, 2014), and causes intrauterine growth restriction (IUGR) (Barut et al, 2010). IUGR affects up to 32% of pregnancies in some developing countries (Ananth and Vintzileos, 2009), and can cause cardiovascular disease in utero and in adulthood (Demicheva and Crispi, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects in placental vascular development can cause embryonic death and abnormal organogenesis, can negatively affect fetal growth and can confer a higher risk of disease in the postnatal life (Barker et al, 1989). For example, defective patterning of the fetoplacental vasculature, also known as the labyrinth, results in abnormal heart development in mouse (Shaut et al, 2008) and human (Demicheva and Crispi, 2014), and causes intrauterine growth restriction (IUGR) (Barut et al, 2010). IUGR affects up to 32% of pregnancies in some developing countries (Ananth and Vintzileos, 2009), and can cause cardiovascular disease in utero and in adulthood (Demicheva and Crispi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, defective patterning of the fetoplacental vasculature, also known as the labyrinth, results in abnormal heart development in mouse (Shaut et al, 2008) and human (Demicheva and Crispi, 2014), and causes intrauterine growth restriction (IUGR) (Barut et al, 2010). IUGR affects up to 32% of pregnancies in some developing countries (Ananth and Vintzileos, 2009), and can cause cardiovascular disease in utero and in adulthood (Demicheva and Crispi, 2014). Understanding the mechanisms controlling development of the placental vasculature is essential to uncover the developmental origins of disease.…”
Section: Introductionmentioning
confidence: 99%
“…FGR fetuses present cardiovascular remodeling already in utero that persist into childhood (4,5). This effect is thought to contribute to their subsequent long-term cardiovascular risk (6). One of the most prominent signs of cardiac remodeling associated with FGR in fetal life and childhood is a more spherical heart measured by lower values on left ventricular sphericity index (LVSI) (5).…”
mentioning
confidence: 99%
“…This concept is particularly relevant when applying these measurements to clinical practice in the assessment of fetal cardiac function for different pathologies [10,16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…This technique has also been shown to be feasible and reproducible in fetuses [3,4], and reference values for TDI annular peak velocities and ratios have been published [5,6,7,8]. Recent studies have also shown that in fetuses, TDI could be a more sensitive tool than the currently applied methods to detect fetal cardiac dysfunction, and the technique has been applied to various fetal pathologies, such as intrauterine growth restriction, hydrops or twin-to-twin transfusion syndrome [3,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%